The Gricean Cooperative Principle: Flouting And Hedging In The Conversations In Joseph Conrad’s The Secret Agent - M.G. Sri Ningsih (Jurnal Inspirasi Pendidikan, 2014)
The Cooperative Principle (CP) proposed by Grice states that a speaker should be cooperative by making the conversational contribution as required. In CP Grice proposes four conversational maxims : Quantity, Quality, Relation, and Manner. Speakers sometimes flout the conversational maxims, so do characters in The Secret Agent. The flouting and hedging the conversational maxims can be done through figures of speech. Key words: the Gricean Cooperative Principle, flouting and hedging, figures of speech, conversations, The Secret Agent.